Heat transfer and fluid flow characteristics of a turbulent wall jet with a wavy wall - Kumari A.; Kumar A. (My University, 2025)
The fluid flow and heat transfer characteristics of a turbulent wavy wall jet have been studied numerically using the low Reynolds number model. The three low Reynolds number models, Realizable, RNG and SST are used for code validation with the experimental results present in the literature for the plane wall jet. The best suited model is used further to study the wavy wall jet. The sinusoidal profile [Formula presented] has been used for the wavy wall, where N is total number of cycles and l is total length of wavy wall. In order to study the influence of amplitude on heat transfer and flow behavior, the wavy wall amplitude has been changed from 0 (plane wall) to 0.8 at an interval of 0.1 and number of cycles kept 10 for all the cases. The Reynolds number of heated jet is kept 15000 by using a slot nozzle of height 20 mm and exit velocity 10.95 m/s. The flow separation and re-circulation zone are studied with the help of pressure gradient (dP/dX) and streamwise velocity gradient (dU/dY) for each case. The results show that the flow remains attached till 0.3 amplitude after that flow gets separated. It is found that for amplitude 0.4, 0.5, 0.6, 0.7 and 0.8, separation starts for the first time at X=56.4,X=41,X=26.3,X=25.9 and X=25.5. The area of re-circulation zone is found to increase as the amplitude of wavy surface increases from 0.4 to 0.8. Also, the maximum streamwise velocity is found to increase with the increase in the amplitude of the wavy wall. These characteristics influenced the average Nusselt number drastically. The average Nusselt number is on the higher side as compared to the case of a plane wall. However, the trend is not monotonic; it increases till amplitude 0.7 and then it decreases. A maximum increase of 19.08% is observed for the wavy wall with amplitude 0.7. The thermal hydraulic performance (THP) is increased by 5.3% for amplitude 0.8 with respect to plane wall jet. © 2020 Elsevier Inc.